Niñez, Género y Escritura: La bolsa amarilla de Lygia Boujunga - Lorca, Jorge; Fuenzalida, Valeria (Revista de Teoría del Arte, 2019)
Abstract.The present study, is the product of a two voices interpretive reading, under the wing of a critical andpoliticized reflection of a seemingly innocuous text, coming from what could prejudicially be thought,a “minor” gender called children’s literature. Our thesis, is that its author, Lygia Bojunga, managesto intelligently stand out from the hegemonic paradigms that dominate the shifting horizon of the ownsubaltern production conditions that characterize this subgenre, to install an overlapping criticalfracture to the normativity of socially stratified roles. In this way, childhood, the feminine, genderroles and writing, emerge as some of the topics chosen and treated here, and that the author managesto disarticulate as the protagonist is suffering and questioning firsthand the naturalization of thesesame normative social practices that relegate her as a girl and as a woman to spaces encrypted by thepower. Without a doubt, the elegance and aesthetic simplicity that the author of “The yellow bag”manages to attach to her work, cohabit in depth with her critical and subversive gaze within that sameinnocent writing that could be thought of as a distracting but falsely inoffensive pyrotechnic effectfrom the reviled and marginal genre of children's literature. Its political component operates preciselythere, where there seems to be no danger in a lowercaliber, non-academic writing, but that cleverly,in a smuggling mechanism, introduces a critical status of the operations of adultcentrism andprevailing androcentrism.